Epistemological analysis of theses and dissertations on special education service: 2000 to 2009 - Casagrande, Rosana Castro (2014)
The general aim of this research was to carry out an epistemological analysis of theses and dissertations on special education service written between 2000 and 2009. The analysis is based on the technical and theoretical dimensions and it uses an adaptation of the Paradigmatic Scheme by Sánchez Gamboa (1987, 2007). Following a qualitative approach, the documentary analysis of 18 theses and dissertations was carried out. The results indicate: 1. At the Technical Level: 2009 was the most prolific year for research on special education service; 72% of all the works were produced in public universities; 44% do not specify the recording techniques; 50% do not specify the type of data analysis; 84% present qualitative procedures; 2. Theoretical Level: the main tackled theme was “Hearing Impairment/Deafness” (27.7%); 61% made use of unspecific methodological approaches and types of changes; 17% are classified as critical and dialectical, and 22% are phenomenological and hermeneutic. Most of the works could not be characterized or classified according to a standard methodological approach in view of their hybrid aspect and due the fact that they do not have a methodological boundary. It is essential to extend research on epistemological analysis so that it can effectively contribute to improving studies and directing them towards praxis.